Role of Self-Efficacy as a Mediator between Negative Emotionality and Resilience in Navy Wives - Wiwik Triwidiyanti; Yusti Probowati Rahayu; Andrian Pramadi (Journal of Educational, Health and Community Psychology, 2023)
Military spouses, particularly wives, require resilience given the various stressors they face, such as the absence of their husbands for support, the dual role of being both a mother and a father, and handling household tasks and childcare alone. Self-efficacy and negative emotionality or neuroticism are often associated with an individual's level of resilience, making them characteristics that can predict a person's resilience effectively. This study aims to test a model of the relationship between self-efficacy, negative emotionality, and resilience in Navy wives, utilizing a quantitative cross-sectional research design. Measurement tools include a modified Resilience Scale of Adult (RSA), the Indonesian version of the Self-Efficacy Scale, and a personality scale translated based on the BFI-2 Indonesian version. The data analysis method employed is Path Analysis using Amos-24. The research results indicate that there is an influence, both directly and indirectly, of the variable negative emotionality (p < 0.05) on resilience. There is a positive influence of self-efficacy (p < 0.05) on resilience, and self-efficacy plays a mediating role in the relationship between negative emotionality and resilience (p < 0.05). The findings suggest that the role of self-efficacy as a protective factor is highly dominant in determining an individual's resilience compared to the role of negative emotionality (a risk factor). Based on the research results, training for the development or enhancement of self-efficacy is recommended for Navy wives to improve their resilience and mental health. Future research is encouraged to explore other variables that enhance self-efficacy, as self-efficacy is a significant factor influencing resilience.